2-Chloroquinoline-3-carbaldehyde modified nanoporous SBA-15-propylamine (SBA-Pr-NCQ) as a selective and sensitive Ag+ ion sensor in aqueous media. (February 2022) - Mohammadi Ziarani, Ghodsi; Moradi, Razieh; Mohajer, Fatemeh; Badiei, Alireza
Abstract: Design and synthesis of a mesoporous silica material functionalized with 2-chloroquinoline-3-carbaldehyde (SBA-Pr-NCQ) were developed. The pore structure of functionalized structure SBA-Pr-NCQ was characterized by different techniques. Fluorescence features of SBA-Pr-NCQ were verified by adding different metal ions in aqueous media and demonstrated good sensitivity and selectivity for Ag + cations. The competition test displayed that the fluorescence response of the structure was specific for Ag + cations. Additionally, the high detection limit of 7.6 × 10 −6 M proved the good linear relationship between the fluorescence intensity of modified structure (SBA-Pr-NCQ) and the concentration of Ag + Graphical abstract: Image 1 Highlights: Design and synthesis of a mesoporous silica material functionalized with 2-chloroquinoline-3-carbaldehyde (SBA-Pr-NCQ). Fluorescence features of SBA-Pr-NCQ were verified by adding different metal ions in aqueous media for Ag + cations. The competition test showed that the fluorescence response of the structure was specific for Ag + cations. The high detection limit of 7.6 × 10 −6 M proved a good linear relationship between the fluorescence intensity of the modified structure (SBA-Pr-NCQ) and the concentration of Ag + .